Synthesis of a metal chelating monomer for radiation polymer dosimetry - Wolfel, Alexis (2021)
To enhance the performance of polymeric dosimeters it is necessary to design novel formulations considering the mechanisms that register the absorbed dose (e.g. induced polymerization) and the readout method. The combination of the advantages of polymeric dosimetry, such as response stability and high sensitivity in a tissue-equivalent material, together with the high optical absorbance commonly found in colored metal-ligand complexes, represents a promissory strategy to achieve new dosimetry systems with enhanced optical properties. Addressing this scope, herein this study reports the synthesis of a vinylic monomer that was polymerized for the first time induced by X-Ray radiation, being also capable of forming highly colored complexes with metal ions. The chelating monomer was obtained from glycidyl methacrylate and iminodiacetic acid, purified and fully characterized. Then, the reactivity of a monomeric system containing the obtained monomer, N-isopropylacrylamide and N,N′-methylenebisacrylamide was evaluated. Two different initiation methods, namely chemically initiated polymerization and X-ray promoted polymerization were compared. Finally, the ability of the obtained polymers to chelate Cu2+ ions and the corresponding changes in their optical properties were studied.